Impact of Weakening Export Competitiveness on Indonesian Textile Industry Layoffs, 2022–2025 - Ratu Aribah Santika Xaviera; Ahmad Devani Yuslah; Alfina Marta; Aisyah Fahriza Anindita; Rara Marcella; Ahmad Setiawan Nuraya (Universitas Budi Luhur, 2026)
The textile and textile products (TPT) industry is a labor-intensive sector that plays a vital role in the Indonesian economy through exports and employment. However, during the 2022–2025 period, the textile industry has faced various pressures, such as declining global demand, increasing competition from other countries, and the entry of cheap imported products. These conditions have weakened the competitiveness of Indonesian textile exports and led to an increase in layoffs in the textile industry. This research aims to analyze the impact of weakened export competitiveness on the surge in layoffs in Indonesia’s textile industry during the 2022–2025 period. This research uses a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS), UN Comtrade, the Ministry of Industry, and the Ministry of Manpower. The analytical methods used are Revealed Comparative Advantage (RCA) and comparative descriptive analysis. The results indicate that Indonesia still holds a comparative advantage in textile exports, as the RCA value exceeds 1. However, Indonesia’s competitiveness remains lower than Vietnam’s, which has a higher RCA value. The weakening of export competitiveness has led to a decline in textile firms’ production, prompting many companies to implement layoffs. Additionally, high production costs, reliance on imported raw materials, and the influx of cheap imported products have further worsened the condition of the national textile industry. Therefore, efforts to improve the competitiveness and efficiency of the industry are necessary to maintain the sustainability of Indonesia’s textile industry.